1992
DOI: 10.1111/j.1540-6261.1992.tb04674.x
|View full text |Cite
|
Sign up to set email alerts
|

The Post‐Merger Performance of Acquiring Firms: A Re‐examination of an Anomaly

Abstract: The existing literature on the post-merger performance of acquiring firms is divided. We re-examine this issue, using a nearly exhaustive sample of mergers between NYSE acquirers and NYSE/AMEX targets. We find that stockholders of acquiring firms suffer a statistically significant loss of about 10% over the five-year post-merger period, a result robust to various specifications. Our evidence suggests that neither the firm size effect nor beta estimation problems are the cause of the negative post-merger return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
246
2
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 841 publications
(296 citation statements)
references
References 24 publications
16
246
2
8
Order By: Relevance
“…However, a growing amount of studies show that the activity of financial markets reflected by movements of stock prices does not always comply with the Efficient Market Hypothesis as determined by Fama [6]. While the results of some studies show that stock markets overreact to news [2], [15], [1], the others observed an underreaction [21], [7], [11]. Thus in many cases the role of information in stock markets could not be determined as unambiguous.…”
Section: Introductionmentioning
confidence: 69%
“…However, a growing amount of studies show that the activity of financial markets reflected by movements of stock prices does not always comply with the Efficient Market Hypothesis as determined by Fama [6]. While the results of some studies show that stock markets overreact to news [2], [15], [1], the others observed an underreaction [21], [7], [11]. Thus in many cases the role of information in stock markets could not be determined as unambiguous.…”
Section: Introductionmentioning
confidence: 69%
“…7 See John, Lang and Netter (1992). 8 For examples, see Agrawal, Jaffe and Mandelker (1999) and Franks, Harris and Titman (1991) for mergers and acquisitions; Kaplan and Weisbach (1992) for divestitures; McConnell and Nantell (1985) for joint ventures. Also see Dyer, Kale and Singh (2001) and Keasler and Denning (2009) for alliances; Allen and McConnell (1998) for carve-outs; Desai and Jain (1999) and Daley, Mehrotra and Sivakumar (1997) for spinoffs.…”
Section: Business and Economic Researchmentioning
confidence: 99%
“…However, despite the implementation of asset reorganization or Huanshuai owners many losses into profit the listed company, shell protection to shield, but may also have negative effects of "invite wolves into the house", which have been adversity losses listed company one disaster after another, finally can only hasten their delisting or bankruptcy. Such as Magenheim and Mueller (1988) compared with the result of test of showed that after the reorganization of the company's performance has declined, Agrawal Jaffe and Mandelker (1992) found company market adjustment performance after reorganization does not rise to fall. However, despite the implementation of asset reorganization or Huanshuai owners many losses into profit the listed company, shell protection to shield, but may also have negative effects of "invite wolves into the house", which have been adversity losses listed company one disaster after another, finally can only hasten their delisting or bankruptcy.…”
Section: Introductionmentioning
confidence: 99%